PREVENTION OF RADICALISM IN THE ERA OF GLOBALIZATION TROUGH DIGITALIZATION OF PANCASILA EDUCATION - Kelvin Rizky Eliant Kamal; Muhammad Ashif (JURNAL SETIA PANCASILA, 2023)
Digitalization has brought significant changes in various aspects of life, including education. Therefore, efforts to prevent radicalism need to be adapted into the context of digitalization of education to confront the existing challenges. This aims to review the importance of the digitalization of Pancasila education as a strategy toprevent radicalism in the era of globalization. Through the descriptive research method, the data was collected from various literature sources that are relevant to the topic. This case shows that the digitalization of Pancasila education can be an effective tool in the prevention of understanding of radicalism in the era of globalization. Digitization enables broader access to Pancasila education materials, facilitating interactions and collaboration between students, and enables the development of content that is relevant to social and cultural realities. In addition, the digitalization of Pancasila education can encourage students to develop critical and analytical thinking skills in dealing with widespread information in the digital space. With the use of proper technology, Pancasila education can teach critical values, pluralism, tolerance, and independence to think which is an important basis in preventing the understanding of radicalism. However, there are also challenges that need to be overcome in implementing the digitalization of Pancasila education. Adequate technological infrastructure is needed, training for educators, as well as effective monitoring and surveillance to prevent the spread of radical content in the digital room. Therefore, the digitalization of Pancasila education has the great potential in the prevention of understanding of radicalism in the era of globalization. By utilizing technology wisely, Pancasila education can become an important instrument in forming a generation that has a strongunderstanding of national values, tolerance, and unity in the face of the challenges of radicalism in the world that are increasingly connected digitally.